1990
DOI: 10.1103/physrevd.42.3591
|View full text |Cite
|
Sign up to set email alerts
|

Helicity and the Aharonov-Bohm effect

Abstract: Conservation of helicity is applied to the scattering of relativistic electrons by an infinitely long solenoid of arbitrarily small radius (Aharonov-Bohm scattering). It is also shown that the Born approximation, which fails when applied to Aharonov-Bohm scattering in the Schrodinger equation formalism, gives correct results in the case of the Dirac equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
4
17
0
Order By: Relevance
“…Subsequently this interaction was attributed to a spin-magnetic moment interaction [6]. The first order Born amplitude for a Dirac particle was calculated in [7] and the second order in [8] where full agreement with the expansions of the exact amplitude [9] to the corresponding order was found. Non-relativistic perturbative calculations within the framework of the field theory models of the AB with spin-1/2 particles suffered no problems [10,11].…”
Section: Introductionmentioning
confidence: 84%
“…Subsequently this interaction was attributed to a spin-magnetic moment interaction [6]. The first order Born amplitude for a Dirac particle was calculated in [7] and the second order in [8] where full agreement with the expansions of the exact amplitude [9] to the corresponding order was found. Non-relativistic perturbative calculations within the framework of the field theory models of the AB with spin-1/2 particles suffered no problems [10,11].…”
Section: Introductionmentioning
confidence: 84%
“…We see from (18) that the vector potential in the noncommutative plane has a component in the radial direction (u r ) which is not present in the standard case. In fact, in polar coordinates we can write…”
Section: The Aharonov-bohm Potential In the Noncommutative Planementioning
confidence: 99%
“…Many approaches were suggested in the literature to remedy this problem for non-relativistic particles, examples of which are [2,4,6,[9][10][11][12][13][14]. When the spin degree of freedom is taken into account [8], it was shown that perturbation theory works for both non-relativistic [13] and relativistic particles [3,16,17]; thanks to the spin-magnetic moment interaction.…”
Section: Introductionmentioning
confidence: 99%